Evaluating the effect of caudal epidural block on optic nerve sheath diameter in pediatric patients: randomized controlled study - Ahmet Murat Yayik; Elif Oral Ahiskalioglu; Erkan Cem Celik; Mirac Selcen Ozkal Yalin; Binali Firinci; Irem Ates; Muhammed Enes Aydin; Ali Ahiskalioglu (BMC Anesthesiology)
Abstract Introduction Caudal epidural block is a widely performed procedure for postoperative pain control of pediatric patients. As the local anesthetic acts by spreading cranially after caudal block, it may lead to several effects on the cerebrospinal fluid and intracranial region. Method Children aged 1–7, ASA I-II were included in this study. The patient population was assigned into two groups as the Caudal Block Group (Group CB) and the Control Group (Group C) Caudal block with 0.25% bupivacaine 1 ml/kg was performed on patients in Group CB. Optic nerve sheath diameter was measured at the following timeline: T0: Following laryngeal mask placement, T1: Following caudal block. T15:15. min, T30:30. min. Heart rate, non-invasive blood pressure, SpO2 and PCO2 values were also recorded at every time point. Results There was no significant difference between two groups considering demographic data, intraoperative hemodynamic parameters, intraoperative SpO2 and PCO2 values. While optic nerve sheath diameter findings were not significantly different between the groups at T0 and T1 points(P > 0.05), the measurements at T15(4.18 ± 0.56 for Group C and 4.62 ± 0.47 for Group CB, P = 0.006) and T30(4.20 ± 0.53 for Group C and 4.76 ± 0.52 for Group CB) were statistically higher in the Caudal Group. Conclusion Evaluation of optic nerve sheath diameter has high diagnostic precision for detecting increased intracranial pressure in children. The findings in this study display that local anesthetic applied for caudal block in pediatric surgeries spread cranially resulting in an increase in the intracranial pressure and optic nerve sheath diameter. However, this increase does not cause intraoperative hemodynamic changes.